PEMANFAATAN TEH KOMBUCHA SEBAGAI OBAT HIPERURISEMIA MELALUI PENURUNAN KADAR 8-HIDROKSI-2-DEOKSIGUANOSIN - Made Baruna Jayadilaga; Ida Bagus Putra Manuaba; Ni Luh Rustini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
The utilization of kombucha tea as hyperuricemia medicine by decreasing levels of 8-hydroxy-2-deoksiguanosin (8-OHdG) has been carried out. This study aimed to determine the ability of kombucha tea to decrease uric acid and 8-OHdG levels in hyperuricemia rats. This research is true experimental with posttest only control group design. Rats that had experienced hyperuricemia were given kombucha tea dose of 10 mL/kg body weight and 40 mL/kg body weight of 4, 8, and 12 days fermentation period. The results showed that kombucha tea can decrease uric acid and 8-OHdG levels in hyperuricemia rats. The best dose of kombucha tea in decreasing uric acid and 8-OHdG levels was 40 mL/kg body weight with 8 days fermentation period. The decrease of uric acid and 8-OHdG levels were 93.88% and 85.89% respectively.